Estudio fenotípico del bovino criollo Casanare biotipo araucano. Análisis zoométrico (2013)
The objective of this investigation was to determine the main body measurements and their differences per farm and sex of Casanare Creole cattle breed in two farms located in the Arauca municipality. 57 animals were used (eigth males and 49 females) and nine body measurements were taken: chest circumference (PT), withers height (ACR), body length (LCO), total length (TL), rump length, (LGR), height at the croup (AGR), anterior hip width (AAG), head width (AC), head length (LC). Data were analyzed with the statistical software R Project package using the Rcmdr and supported by CRAN extensions for the same. For analysis of signifi cance between farms and between nominal variables, a “t” text was applied to evaluate sex differences. The average per farm were 161.3 ± 12.5 cm (LCO), 126.1 ± 8.9 cm (LT), 49.1 ± 3.7 cm (LC) and 19.5 ± 1.8 cm (AC) with statistical differences (P<0.05), while the average for males and females were 53 ± 3.9 cm and 48.6 ± 3.3 cm (LC) and 20.4 ± 2.15 cm and 19.3 ± 1.8 cm (AC) with statistical differences (P<0.05). It was determined that native Araucanian biotype Casanare cattle are animals with medial body proportions (brevilineal) and rated oligometric by their body weight. © 2013, Instituto Nacional de Investigaciones Agricolas (INIA). All Rights Reserved.